PENGARUH LAMA FERMENTASI KEDELAI TERHADAP KARAKTERISTIK SERE KEDELE - Walianingsih, Eka Jana; Jambe, AAGN Anom; Permana, Dewa Gde Mayun (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2016)
This study was aimed to determine the effect of soybean fermentation time for producing the best characteristics of sere kedele . The Completely Randomized Design (CRD) was used for analysis the data resulted by 5 period of fermentation time (12, 18, 24, 30 and 36 h) as a treatment with 3 repetition. The results showed that fermentation time was significantly effected (P<0,05) to water, protein, fat, and carbohydrate content, except to ash content, and all sensory properties of sere kedele (color, taste, flavor, texture, and overall acceptance). The best characteristic of sere kedele was obtained by fermentation for 30 hours, with 9.07% of moisture content, 5.42% of ash content, 28.25% of protein content, 26.29% of fat content, and 30.97% of carbohydrate levels and sensory properties were 5.40 (rather like) for color, 5.40 (rather like) for aroma, 5.70 (like) for sense, 5.15 (rather like) for texture and overall acceptance of 5.20 (rather like) based on proximate analysis (water, ash, protein, fat, carbohydrate) and sensory properties.
Keywords: sere kedele, soybean, fermentation time, characteristics